2014
DOI: 10.1111/jvim.12449
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Intravenous Infusion of Insulin in Diabetic Cats

Abstract: BackgroundRemission occurs in 10–50% of cats with diabetes mellitus (DM). It is assumed that intensive treatment improves β‐cell function and increases remission rates.HypothesisInitial intravenous infusion of insulin that achieves tight glycemic control decreases subsequent insulin requirements and increases remission rate in diabetic cats.AnimalsThirty cats with newly diagnosed DM.MethodsProspective study. Cats were randomly assigned to one of 2 groups. Cats in group 1 (n = 15) received intravenous infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
6
2
Order By: Relevance
“…Compared with the results of other studies of diabetic cats, the remission rates in the present investigation were relatively low in both groups. Other studies have followed diabetic cats for longer periods of time (eg 6 months) than our study (4 months), and it therefore is possible that more cats would have achieved remission if the study had been longer. In addition, it is known that the rate of remission is higher if diabetic cats have received corticosteroids before diagnosis of DM .…”
Section: Discussionmentioning
confidence: 81%
“…Compared with the results of other studies of diabetic cats, the remission rates in the present investigation were relatively low in both groups. Other studies have followed diabetic cats for longer periods of time (eg 6 months) than our study (4 months), and it therefore is possible that more cats would have achieved remission if the study had been longer. In addition, it is known that the rate of remission is higher if diabetic cats have received corticosteroids before diagnosis of DM .…”
Section: Discussionmentioning
confidence: 81%
“…None of the cats had clinical signs compatible with pancreatic or gastrointestinal disease. The present study is part of a previously pubished study (Data S1) …”
Section: Resultsmentioning
confidence: 99%
“…Insulin glargine used over a 4-month period resulted in diabetic remission in 8 of 8 cats (100%), whereas only 3 of 8 cats (38%) treated with PZI and 2 of 8 cats (25%) treated with Lente insulin achieved remission (Marshall et al, 2009). Other studies using insulin glargine were not able to repeat the high treatment success: remission rates ranged between 17% and 47% (Boari et al, 2008;Hall et al, 2009;Hafner et al, 2011). In an Internet-based study using 55 diabetic cats from a German diabetes forum, a remission rate of 64% was achieved (Roomp and Rand, 2009).…”
Section: Long-acting Insulin Analoguesmentioning
confidence: 91%
“…The currently available studies, which have included information on remission, are difficult to compare, because they differ with regard to definition of remission, inclusion criteria of cats, blood glucose targets, and monitoring protocols, as well as type of insulin and type of diet. Published remission rates vary between 13% and 100% (Nelson et al, 1999;Bennett et al, 2006;Martin and Rand, 2007;Boari et al, 2008;Michiels et al, 2008;Marshall et al, 2009;Roomp and Rand, 2009;Hall et al, 2009;Zini et al, 2010;Hafner et al, 2011;Tschuor et al, 2011). It has been suggested that remission rates are higher in cats when treated with newer types of insulin (e.g., insulin analogues such as glargine or detemir) than with other/older types of insulin (e.g., Lente type) (Marshall et al, 2009;Roomp and Rand, 2009;.…”
Section: Remission Of Diabetes In Catsmentioning
confidence: 95%